Integrated Analysis of lncRNAs, mRNAs, and TFs to Identify Regulatory Networks Underlying MAP Infection in Cattle - Heidari, Maryam; Pakdel, Abbas; Bakhtiarizadeh, Mohammad Reza; Dehghanian, Fariba (Frontiers in Genetics, 2021)
Johne’s disease is a chronic infection of ruminants that burdens dairy herds with a significant economic loss. The pathogenesis of the disease has not been revealed clearly due to its complex nature. In order to achieve deeper biological insights into molecular mechanisms involved in Johne’s disease, a system biology approach was used. As far as is known this is the first study that considers lncRNAs, TFs and mRNAs, simultaneously, to construct an integrated gene regulatory network involved in JD. Weighted gene co-expression network analysis (WGCNA) and functional enrichment analysis were conducted to explore co-expression modules from which non-preserved modules had altered connectivity patterns. After identification of hub and hub-hub genes as well as TFs and lncRNAs in the non-preserved modules, integrated networks of lncRNA-mRNA-TF were constructed, and cis and trans targets of lncRNAs were identified. Both cis and trans targets of lncRNAs were found in eight non-preserved modules. Twenty-one of 47 non-preserved modules showed significant biological processes related to the immune system and Johne’s disease. Of these, green, royalblue, purple, darkturquoise, and white non-preserved modules were detected to be potentially related to Johne’s disease in terms of their enriched biological terms, hub and hub-hub genes. Some of the Johne’s related pathways in these modules comprise “positive regulation of cytokine-mediated signaling pathway,” “negative regulation of leukocyte migration,” “T cell differentiation,” “neutrophil activation,” and “defense response”. Furthermore, several genes were identified in these modules, including APLP2, VDR, SLC11A1, PTGER4, RUNX3, MAPK8IP1, TLR4, IL10RA, ALOX5AP, CORO1A, IRF1, BOLA-DMB, and BOLA-DMA, which are potentially associated with Johne’s pathogenesis. This study not only enhanced our knowledge of molecular mechanisms behind Johne’s disease but also highlighted several promising hub and hub-hub genes as prognostic and therapeutic targets for this disease.